Modulation of β1A Integrin Functions by Tyrosine Residues in the β1 Cytoplasmic Domain - Sakai, Takao (The Rockefeller University Press, 1998)
β1A integrin subunits with point mutations of the cytoplasmic domain were expressed in fibroblasts derived from β1-null stem cells. β1A in which one or both of the tyrosines of the two NPXY motifs (Y783, Y795) were changed to phenylalanines formed active α5β1 and α6β1 integrins that mediated cell adhesion and supported assembly of fibronectin. Mutation of the proline in either motif (P781, P793) to an alanine or of a threonine in the inter-motif sequence (T788) to a proline resulted in poorly expressed, inactive β1A. Y783,795F cells developed numerous fine focal contacts and exhibited motility on a surface. When compared with cells expressing wild-type β1A or β1A with the D759A activating mutation of a conserved membrane–proximal aspartate, Y783,795F cells had impaired ability to transverse filters in chemotaxis assays. Analysis of cells expressing β1A with single Tyr to Phe substitutions indicated that both Y783 and Y795 are important for directed migration. Actin-containing microfilaments of Y783,795F cells were shorter and more peripheral than microfilaments of cells expressing wild-type β1A. These results indicate that change of the phenol side chains in the NPXY motifs to phenyl groups (which cannot be phosphorylated) has major effects on the organization of focal contacts and cytoskeleton and on directed cell motility.